The synthesis and characterization of novel rhodium alkenyl complexes and rhodacycloalkanes - Hager, Emma (Department of Chemistry, 2024)
The rhodium dimers [Cp*RhChh and [Cp*RhBr2h were reacted with alkenyl Grignard reagents MgBr(CH2)nCH=CH2 (n = 1 - 4, 6, 8, 9) in an attempt to form bis-alkenyl complexes that would be potential precursors to rhodium-containing metallacycloalkanes. The shorter-chain Grignard reagents (n = 1 - 3) produced novel rhodium allylic complexes of composition Cp*RhBr(1i3-allyl-R) where R = H, CH3, CH2CH3. These were isolated as stable crystals and were fully characterized by analytical and spectroscopic methods. An X-ray crystal structure obtained for one of the complexes (R = CH2CH3) confirmed the allylic structure of the complex. The use of longer-chain reagents (n = 3, 4, 6, 8, 9) resulted in the fonnation of the novel bis-alkenyl complexes Cp*Rh(CH2nCH=CH2)2(H2O). The bis-alkenyl complexes were obtained as yellow oils that were found to be stable in air and non-chlorinated solvents, but unstable in chlorinated solvents. They were characterized by NMR, MS and elemental analysis. Ring-closing metathesis (RCM) reactions were carried out on two of the bis-alkenyl complexes (n = 4, 6) in the presence of Grubbs' first-generation catalyst. NMR evidence indicated that the corresponding 11- and 15-membered ring rhodacycloalkenes had been formed. The rhodium phosphine precursors Cp*RhCh(PR3) (PR3 = PPh3, PMePh2, PMe2Ph) were prepared and reacted with the di-Grignard reagents MgBr-(CH2)n-MgBr (n = 7, 8, 9) to form a series of medium-sized rhodacycloalkanes that were larger than any synthesized previously. The rhodacycles were found to be quite unstable at room temperature. Thermal decomposition studies were conducted on some of the complexes and the major organic products were analyzed by GC-MS. In most cases the major products were 1- and 2-alkenes and n-alkanes. It was found that the nature of the tertiary phosphine ligand affected the types of decomposition products formed.